The gods of Gotham - Faye, Lyndsay (G.P. Putnam's Sons, 2012)
New York City, 1845. Timothy Wilde, a 27-year-old Irish immigrant, joins the newly formed NYPD and investigates an infanticide and the body of a 12-year-old Irish boy whose spleen has been removed.